2023
DOI: 10.3389/fonc.2023.1154631
|View full text |Cite
|
Sign up to set email alerts
|

High VISTA expression is linked to a potent epithelial-mesenchymal transition and is positively correlated with PD1 in breast cancer

Abstract: Breast cancer is the most common type of tumor in women worldwide. Immune checkpoint inhibitors, particularly anti-PDL1, have shown promise as a therapeutic approach for managing this disease. However, this type of immunotherapy still fails to work for some patients, leading researchers to explore alternative immune checkpoint targets. The Ig suppressor of T cell activation domain V (VISTA) has emerged as a novel immune checkpoint that delivers inhibitory signals to T cells and has demonstrated encouraging res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 62 publications
2
2
0
Order By: Relevance
“…Figure 4 shows the co-expression patterns of VISTA with either VSIG8, VSIG3, PSGL-1, or PD-L1 as a positive control. A small correlation between VISTA and PD-L1 mRNA expression was observed, consistent with their known overexpression in multiple cancer types (He et al, 2021;Rezouki et al, 2023). A strong correlation was found between VISTA and PSGL-1 across various cancer types (Figure 4D and SI Figure 3), suggesting a functional connection and supporting a cis interaction-dependent relationship between VISTA and PSGL-1.…”
Section: Vista Engages With Vsig3 Vsig8 and Psgl-1 In Cis Interactionssupporting
confidence: 73%
“…Figure 4 shows the co-expression patterns of VISTA with either VSIG8, VSIG3, PSGL-1, or PD-L1 as a positive control. A small correlation between VISTA and PD-L1 mRNA expression was observed, consistent with their known overexpression in multiple cancer types (He et al, 2021;Rezouki et al, 2023). A strong correlation was found between VISTA and PSGL-1 across various cancer types (Figure 4D and SI Figure 3), suggesting a functional connection and supporting a cis interaction-dependent relationship between VISTA and PSGL-1.…”
Section: Vista Engages With Vsig3 Vsig8 and Psgl-1 In Cis Interactionssupporting
confidence: 73%
“…These data are presented in Figure 5 and the top 100 differentially expressed genes are listed in Tables S5 and S6. The results of this analysis confirmed that the paclitaxel-resistant cells in cluster 1 (depicted in orange in Figure 5a) resided in a highly mesenchymal state, since, besides the mesenchymal signature described above (Section 2.1), they also overexpressed genes known to induce EMT, including S100A4 [34,35], C10orf54 [36], and WISP1 [37] (Figure 5b). Therefore, it is reasonable to assume that the EMT pathway is involved in the resistance phenotype of these cells and its targeting [38] may be a viable option to restore drug sensitivity.…”
Section: Heterogeneity In the Chemoresistant Tnbc Populations Reflect...supporting
confidence: 66%
“…VISTA is an immunological checkpoint protein, and its overexpression, together with increased levels of the VSIG3 and PSGL-1 receptors in the tumor microenvironment, may be involved in the modulation of immune responses to cancer. There is growing evidence of the importance of the immunosuppressive role of VISTA in cancer progression [ 20 , 41 , 57 , 62 , 63 , 69 73 ]. The presence of VISTA on the surface of cancer cells can not only modulate immune cells but also potentially play a much broader role in cancer biology.…”
Section: Discussionmentioning
confidence: 99%